Uraemic optic neuropathy – a rare presentation of uraemia - Solarin, Adaobi Uzoamaka; Adesanya, Adetola M; Adekunle, Moturayo; Oladimeji, Alaba; Gbelee, Olusegun Henry; Animashaun, Barakat Adeola (African Journal of Nephrology, 2018)
Uraemic optic neuropathy (UON) is an acute but reversible loss of vision in patients with end-stage renal failure. Hypoperfusion of the posterior ciliary arteries, the major blood supply to the optic nerve head, results in ischaemic injury to the nerve. Anaemia, hypertension and elevated nitrogen urea level have been identified as factors contributing to optic nerve neuropathy. Toxic uraemic metabolites affect nerve conduction and their removal with dialysis results in improved vision. Optic neuropathy is a rare complication of uraemia in children. This is the first case of optic neuropathy related to uraemia in a child with end-stage renal disease in Nigeria.